Effects of Remote Ischemic Conditioning on Cerebral Hemodynamics in Ischemic Stroke - Qin C (Dove Medical Press, 2020)
Chen Qin,1,* Xiuli Yan,1,* Hang Jin,1 Ruyi Zhang,2 Yaode He,1 Xin Sun,1 Yihe Zhang,1 Zhen-Ni Guo,1,3 Yi Yang1,3 1Department of Neurology, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 2Department of Cardiovascular Center, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China; 3Clinical Trial and Research Center for Stroke, Department of Neurology, The First Hospital of Jilin University, Changchun 130021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Yang; Zhen-Ni GuoDepartment of Neurology, The First Hospital of Jilin University, Xinmin Street 1#, Changchun 130021, People’s Republic of ChinaTel +86-13756661217; +86-18186872986Fax +86-431-88782378; +86-431-88782378Email doctoryangyi@163.com; zhen1ni2@163.comAbstract: Ischemic stroke is one of the most common cerebrovascular diseases and is the leading cause of disability all over the world. It is well known that cerebral blood flow (CBF) is disturbed or even disrupted when ischemic stroke happens. The imbalance between demand and shortage of blood supply makes ischemic stroke take place or worsen. The search for treatments that can preserve CBF, especially during the acute phase of ischemic stroke, has become a research hotspot. Animal and clinical experiments have proven that remote ischemic conditioning (RIC) is a beneficial therapeutic strategy for the treatment of ischemic stroke. However, the mechanism by which RIC affects CBF has not been fully understood. This review aims to discuss several possible mechanisms of RIC on the cerebral hemodynamics in ischemic stroke, such as the improvement of cardiac function and collateral circulation of cerebral vessels, the protection of neurovascular units, the formation of gas molecules, the effect on the function of vascular endothelial cells and the nervous system. RIC has the potential to become a therapeutic treatment to improve CBF in ischemic stroke. Future studies are needed to highlight our understanding of RIC as well as accelerate its clinical translation.Keywords: remote ischemic conditioning, cerebral hemodynamics, ischemic stroke, cerebral blood flow